Evaluating the Impact of Customer Service Quality on Customer Satisfaction at XYZ Company - Syafrina, Mia; Siregar, Purnama Ramadhani (Journal of Applied Business Administration, 2024)
This study examines the impact of service quality on customer satisfaction at XYZ Company, with a specific focus on the role of customer service. Using quantitative methods, the study sampled 100 respondents. The research involved testing the validity and reliability of questionnaire instruments, and data analysis included multiple linear regression, t-tests, and F-tests. The findings reveal that, overall, service quality significantly affects customer satisfaction. Specifically, reliability, responsiveness, assurance, and tangibles have a significant impact, while empathy does not. This research contributes valuable insights for developing marketing and service management strategies to enhance customer satisfaction and offers data-driven guidance for gaining a competitive edge.